PEMBENTUKAN KONSEP DIRI SISWA SMA MELALUI MEDIA SOSIAL INSTAGRAM - Pratama, Ricky Zikrillah; Mudjiyanto, Bambang; Sitinah, Sitinah; Fernando, Joshua; Sandi, Fitriana (FISIP IBI-K57 Prodi Komunikasi, 2020)
The development of social media, especially Instagram, is increasingly favored by young people. The resulting content seems to represent the self-concept of its users. This study aims to analyze the formation of self-concept of SMA Negeri 8 Jakarta students through social media Instagram. This study uses the theory of Uses and Gratifications and qualitative descriptive methods using observation, interviews, and collecting documentation as secondary data. The results of this study indicate that there are two reasons for self-concept formation in students of SMA Negeri 8 Jakarta in fulfilling their needs in using media, namely social integrity needs, and cognitive needs. Furthermore, the informants also have three characteristics of self-concept, namely: self-conclusive, self-protective, and real and ideal, true, and false selves. The things that can shape their self-concept are likes, comments, and the content they share, for the followers are not too important. Informants are more confident in interacting on the Instagram application than directly because Instagram users do not meet face to face dir